Direction of Islamic Law Compilation Reform: Efforts to Codify Indonesian Islamic Family Law - Prima Angkupi; Muhammad Shofwan Taufiq (SMART: Journal of Sharia, Traditon, and Modernity, 2025)
This article examines the problems and new directions of the reform of the Compilation of Islamic Law (KHI) towards the codification of the Islamic Family Law Law. KHI nevertheless has problems, the absence of a formal legislative process and a textualistic fiqh approach make the norms in the KHI less responsive to issues such as justice, equality and the social dynamics of Indonesian Muslim society. This article aims to identify the normative and legal roots of the KHI, as well as the legal political strategies that can be used to transform it into an Islamic Family Law Act in the national legal system. This research is a literature study with a historical and doctrinal approach, using Mahfud MD legal political theory and Jasser Auda maqāṣid al-syari’ah. The first finding shows that the legal position of the KHI is weak because it does not have a legitimate legislative basis in the post-reform national legal system, and its substance reflects a patriarchal construction that is not in line with constitutional values. The second finding shows that the renewal requires a legal political strategy that is transformational, multidisciplinary and participatory, therefore that the resulting Islamic family law is not only legally-formally valid, owever also socially legitimate and substantively just.